2015
DOI: 10.1021/acs.iecr.5b02478
|View full text |Cite
|
Sign up to set email alerts
|

S-PVC Grain Morphology: A Review

Abstract: Among the properties required for producing PVC resin of good quality, the particle morphology (size, primary particles, agglomerates, skins, pores, etc.) plays an important role in processing and performance of products. Three main physical transitions are involved in self-structuring the grains of suspension PVC: nucleation, aggregation and growth. All of these processes are affected by many physical transitions and chemical phenomena that are inter-related and many are complex functions of polymerization co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…Among works performed on the enhanced productivity of PVC through temperature-trajectory [2][3][4][5][6][7][8], in earlier work [9][10][11] we suggested the most reduction in the polymerization time up to 33%. Bijanmanesh et al [13] reported that continuous dosing of a fast initiator during suspension polymerization of vinyl chloride enhanced productivity by 40%.…”
Section: Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…Among works performed on the enhanced productivity of PVC through temperature-trajectory [2][3][4][5][6][7][8], in earlier work [9][10][11] we suggested the most reduction in the polymerization time up to 33%. Bijanmanesh et al [13] reported that continuous dosing of a fast initiator during suspension polymerization of vinyl chloride enhanced productivity by 40%.…”
Section: Methodsmentioning
confidence: 87%
“…By comparing these micrographs, it can be seen that the PVC grains prepared by Cok-PVC conditon are more spherical with smoother surfaces than those produced by control condition. the thick sorrounding skin as well as the uniform and large size of primary particles inside grains forming a kind of strong inner skeleton prevent the droplet from collapsing [9]. The larger primary particles in size and number at the early stage of the reaction, are more likely to collides to the inner surface of the droplets and thus strengthens the skin [10].…”
Section: Effect On Grain Shapementioning
confidence: 99%
See 3 more Smart Citations